Nurses’ Opinions Regarding Comments from a Patient Safety Culture Evaluation - Ismail , Moamen Abdelfadil; Al-Ezzi, Sharifa Omar Ahmad; Alanazy , Maryam Nazal; Al-Enazi , Amerah Ghazi Saleh; Alotaibi , Abdullah Hathal Munif; Alghamdi, Ibrahem saleh abadh; Al-Jizani, Fawzia Saeed Hassan; KABi , SABAH AHMAD yAHyA; AL SHAMMARI, NAWAF Hammod NAWMN; ALSHMMARI, MOHMMAD AWWAD GHANIM; Al suhaymi, Barakah Ali; Al suhaymi, Jehan Ali (Journal of Ecohumanism, 2024)
Background: Ensuring a strong patient safety culture is essential for the delivery of high-quality healthcare. In low- and middle-income countries (LMICs), inadequate and unsafe medical care is responsible for nearly 60% of fatalities, many of which are preventable. A positive patient safety culture fosters trust, openness, and performance improvement. Understanding healthcare workers’ perceptions of safety practices is a crucial step in enhancing patient safety culture. Methods: This study was conducted using a self-administered online survey among 1000 healthcare professionals in a major general hospital. The Hospital Survey on Patient Safety Culture (HSOPSC) was utilized, assessing 42 items across 12 dimensions of patient safety culture. 700 responses were analyzed. Descriptive statistics, positive response percentages, and multiple linear regression were used for data analysis. Results: Overall, 76.9% of respondents rated the patient safety grade as excellent or very good. The patient safety culture composite score was 74.2%, with strengths in areas like "Teamwork within units" (91.3%) and "Organizational learning" (88.4%). However, areas needing improvement included "Staffing" (49.4%) and "Non-punitive response to errors" (53.1%). A majority of respondents (67.1%) had not reported any safety events in the past year. Female healthcare workers and nurses reported lower perceptions of patient safety compared to male and physician respondents. Additionally, work area/unit influenced perceptions, with emergency and surgery departments having better safety perceptions. Conclusion: The study highlights a generally positive perception of patient safety culture in the hospital, though areas such as staffing and non-punitive responses to errors require improvement. Gender, position, and work area/unit were significant predictors of safety perceptions. These findings emphasize the need for targeted interventions to enhance patient safety culture, with a focus on improving staffing and fostering a non-punitive environment for reporting errors.